2023
DOI: 10.1021/acs.energyfuels.3c01513
|View full text |Cite
|
Sign up to set email alerts
|

Experimental and Modeling Study of Water Imbibition and Flowback in Shale: Prediction of Relative Permeability and Capillary Pressure Curves

Abstract: Understanding the invasion and flowback processes of water, as the main source of hydraulic fracking fluid, is crucial for the proper evaluation and development of complex gas shale formations. Direct measurements of full gas−water relative permeability and capillary pressure curves by steady-state or unsteady-state techniques are not feasible in ultralow permeability shales. Therefore, the objective of this study is to investigate the dynamic rock−fluid properties of a Mancos shale sample by mimicking water i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 63 publications
(116 reference statements)
0
1
0
Order By: Relevance
“…Meanwhile, the capillary pressure is affected by permeability, pore structure, wettability, and other factors of coal or rock 28,29 . The capillary pressure in low‐permeability rock formations is often very high, which impacts the oil and gas recovery 30–32 . Yassin et al found that capillary pressure is significantly affected by reservoir wettability and microscopic pore structure 33 .…”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile, the capillary pressure is affected by permeability, pore structure, wettability, and other factors of coal or rock 28,29 . The capillary pressure in low‐permeability rock formations is often very high, which impacts the oil and gas recovery 30–32 . Yassin et al found that capillary pressure is significantly affected by reservoir wettability and microscopic pore structure 33 .…”
Section: Introductionmentioning
confidence: 99%